A systematic review and meta-analysis of the effects of educating parents on the benefits and schedules of childhood vaccinations in low and middle-income countries - Lungeni Auguy Lukusa; Valantine Ngum Ndze; Nyanyiwe Masingi Mbeye; Charles Shey Wiysonge (Taylor & Francis Group, 2018)
Public health benefits of childhood vaccinations risk being derailed by low vaccination coverage in low and middle-income countries. One reason for the low coverage is poor parental knowledge of the importance of completing vaccination schedules. We therefore assessed the effects on childhood vaccination coverage, of educating parents and other persons assuming the parental role. We prospectively registered the systematic review, published the protocol, and used standard Cochrane methods to collect and synthesise the evidence. We found six eligible randomised trials with 4248 participants. Three trials assessed health-facility based education of mothers on the importance of completing vaccination schedules; immediately after birth and three months later (one study) or during the first vaccination visit (two studies). The other trials assessed community-based education, including information campaigns on the importance of vaccines using audiotaped presentations and leaflet distributions (one study); structured group discussions on benefits and costs of childhood vaccination and local action plans for improving vaccine uptake (one study); and home-based information sessions using graphic cards showing benefits and costs of childhood vaccinations and location of vaccination centres (one study). Combining the data shows that these interventions lead to substantial improvements in childhood vaccination coverage (relative increase 36%, 95% confidence interval 14% to 62%). There was no difference between the effects of community-based and facility-based education. Therefore, education in communities and health facilities on the importance of childhood vaccinations should be integrated into all vaccination programmes in low and middle-income countries; accompanied by robust monitoring of impacts and use of data for action.